Automated Quantification of the Subcellular Localization of Multicompartment Proteins via Q‐SCAn. (10th October 2013) - Bauer, Nicholas C.; Corbett, Anita H.; Doetsch, Paul W.
Abstract : In eukaryotic cells, proteins can occupy multiple intracellular compartments and move between compartments to fulfill critical biological functions. Unfortunately, no methods have been developed to robustly measure the distribution of a protein among compartments. To address this need, we have developed an automated method termedq uantitatives ubcellularc ompartmentalizationan alysis (Q‐SCAn). Q‐SCAn is a quantitative analytical tool for providing broader and more detailed analysis of the localization of multicompartment proteins as compared to the currently available approaches. Abstract : In eukaryotic cells, proteins can occupy multiple intracellular compartments and even move between compartments to fulfill critical biological functions or respond to cellular signals. Examples include transcription factors that reside in the cytoplasm but are mobilized to the nucleus as well as dual‐purpose DNA repair proteins that are charged with simultaneously maintaining the integrity of both the nuclear and mitochondrial genomes. While numerous methods exist to study protein localization and dynamics, automated methods to quantify the relative amounts of proteins that occupy multiple subcellular compartments have not been extensively developed. To address this need, we present a rapid, automated method termedq uantitatives ubcellularc ompartmentalizationan alysis (Q‐SCAn). To develop this method, we exploited the facile molecular biology of the budding yeast, Saccharomyces cerevisiae . Individual subcellular compartments are defined by a fluorescent marker protein and the intensity of a target GFP‐tagged protein is then quantified within each compartment. To validate Q‐SCAn, we analyzed relocalization of the transcription factor Yap1 following oxidative stress and then extended the approach to multicompartment localization by examining two DNA repair proteins critical for the base excision repair pathway, Ntg1 and Ung1. Our findings demonstrate the utility of Q‐SCAn for quantitative analysis of the subcellular distribution of multicompartment proteins .